The Effect of Reciprocal Teaching Technique Toward the Students’ Ability in Reading Narrative Text - Sugianto; Sopian Saori (Journal of English Education and Literature, 2024)
The observation at SMAN 1 Sikur shows that students' reading ability is still low so that appropriate intervention is needed in the learning process. Low reading ability can adversely affect students' comprehension of narrative text, hinder the development of knowledge, and reduce students' ability to express ideas both in writing and orally. This study aims to determine the effectiveness of reciprocal technique on students' narrative text reading ability. This research is focused on the XI grade students of SMAN 1 Sikur in the academic year 2023/2024. The research method that will be conducted in this research is quasi experiment with experimental research type. The research design in this research is Pretest Posttest Control Group Design. In this design, there will be two sample classes, one sample for the experimental group, which is the subject group in the form of applying the reciprocal technique in learning to read narrative text, while the control group is treated with conventional learning techniques. Samples are taken as part of the overall research object and are considered to represent the true picture of the population. The sample of the research is 62 students, (31 students of experimental class and 31 students of control class). The average score of the experimental class was 2.158. While the average value of the control class was 2.230. In accordance with the analysis above, the researcher found that Reciprocal Teaching Technique has a significant effect on the ability to read narrative text of students in grade XI of SMAN 1 Sikur. This is evidenced by the significant difference in the average post- test scores of the experimental and control groups. This conclusion can be seen from the results of statistical calculations, that the "sig" value is smaller than "0.05".